2006
DOI: 10.1007/s10342-006-0143-5
|View full text |Cite
|
Sign up to set email alerts
|

Species richness and biomass of understory vegetation in a Eucalyptus globulus Labill. coppice as affected by slash management

Abstract: The aim of this study was to assess the effect of different slash management practices on understory biodiversity and biomass in Eucalyptus globulus coppices in Central Portugal. The experiment consisted of four treatments: (a) removal of slash (R), (b) broadcast over the soil (S), (c) as in S but concentrating woody residues between tree rows (W) and (d) incorporation of slash into soil by harrowing (I). Understory vegetation was surveyed during 1-6, 9, and 10 years, the proportion of soil cover by plant spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…The number of shrub species was very close to the previous research result (13-23 species) [37]. Carneiro et al [38] found that the average number of understory species was 6-15 in Eucalyptus plantations aged 1 and 10 years old. Luo et al [39] also found the diversity of shrub species was similar among subtropical plantations in southern China.…”
Section: Effects Of Plantation Typesupporting
confidence: 73%
“…The number of shrub species was very close to the previous research result (13-23 species) [37]. Carneiro et al [38] found that the average number of understory species was 6-15 in Eucalyptus plantations aged 1 and 10 years old. Luo et al [39] also found the diversity of shrub species was similar among subtropical plantations in southern China.…”
Section: Effects Of Plantation Typesupporting
confidence: 73%
“…However, such a trend was not statistically significant when analysed by linear regression. Variation in the number of species over time in previous studies performed in eucalyptus plantations in Central Portugal has been partially explained by the scarcity or abundance of winter and spring rainfall (Fabião et al, 2002;Carneiro et al, 2007). 11.5 a 9.5 ab 7.0 b 6.5 b…”
Section: Number Of Speciesmentioning
confidence: 97%
“…In Portugal, some studies have described the dynamics of understory vegetation over the 1st year following establishment of a eucalyptus plantation (Fabião et al, 2002;Carneiro et al, 2007). However, these studies focused on the effect of soil preparation techniques and harvest residue management related to the intensity of site preparation on understory vegetation.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, the assumption did not have a negative effect on biodiversity as the removal of harvesting residues has been proven not to reduce understory species diversity (Carneiro et al 2007). …”
Section: Discussionmentioning
confidence: 99%